2023
DOI: 10.1111/jocd.15835
|View full text |Cite
|
Sign up to set email alerts
|

A study on the delayed effect of tilapia skin collagen on skin aging for mice and its possible mechanism

Abstract: ObjectiveStudy the possible mechanism and delayed effect of tilapia skin collagen on skin aging for mice.Materials and MethodsKunming (KM) mice were randomly divided into the aging model group, the normal group, the positive control group (vitamin E) and the low, medium, high dose tilapia skin collagen groups (2.0, 4.0, 8.0 mg/g). The normal group was only injected with saline at the back and the neck. The other groups were injected subcutaneously with 5% D‐galactose and ultraviolet light jointly to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, studies have demonstrated that fish skin collagen is a valuable source of bioactive peptides, characterized by its protein composition and amino acid distribution. Peptides derived from tilapia skin have been found to exhibit antioxidant (Ma et al., 2022), anti‐aging (Pu & Qu, 2023), hypotensive (Chen et al., 2019), hypoglycemic (Liu et al., 2022), and hypolipidemic (Ning et al., 2017) properties. However, few studies on dual inhibitory peptides of ACE and DPP‐IV from tilapia skin have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that fish skin collagen is a valuable source of bioactive peptides, characterized by its protein composition and amino acid distribution. Peptides derived from tilapia skin have been found to exhibit antioxidant (Ma et al., 2022), anti‐aging (Pu & Qu, 2023), hypotensive (Chen et al., 2019), hypoglycemic (Liu et al., 2022), and hypolipidemic (Ning et al., 2017) properties. However, few studies on dual inhibitory peptides of ACE and DPP‐IV from tilapia skin have been reported.…”
Section: Introductionmentioning
confidence: 99%